Fetal therapy in fetal thyrotoxicosis: A case report - Kasemsri Srisupundit (2018)
Introduction: Fetal thyrotoxicosis, often caused by maternal Grave's disease, can have adverse effects on fetal outcomes, such as growth impairment or fetal hydrops. Therefore, intrauterine treatment is recommended. Objective: To describe the experience of intrauterine medical treatment of fetal thyrotoxicosis. Case: A 19-year-old woman with a history of Grave's disease in a euthyroid clinical status after subtotal thyroidectomy became pregnant 2 months after thyroidectomy. At gestational age 28 weeks, persistent fetal tachycardia was identified and the diagnosis of fetal thyrotoxicosis was established by fetal thyroid function test on umbilical cord blood obtained by cordocentesis. Intrauterine treatment for hyperthyroidism was initiated with antithyroid drugs (150 mg/day of propylthiouracil) via maternal oral administration. Fetal heart rate, size of fetal thyroid gland and umbilical cord blood sampling for thyroid function test were monitored. Fetal heart rate became normal and fetal thyroid function tested on fetal cord blood at 1 month after antithyroid fetal therapy was also normal. Fetal thyrotoxicosis improved but the mother had some degree of hypothyroidism from fetal therapy and needed thyroid hormone replacement. The remaining course of gestation was uneventful. The patient had spontaneous labor and delivery at 38 weeks of gestation resulting in normal female baby, 2,900 g, and had no clinical of neonatal thyrotoxicosis. Maternal thyroid medications were stopped immediately after birth. Conclusion: Intrauterine treatment of fetal thyrotoxicosis with medication via the maternal circulation can possibly improve fetal outcome. Copyright © 2007 S. Karger AG.